UHPLC-APCI-TQ-MS analytical method to quantify nitrosamine impurities in the commercial formulation of metformin and glipizide. Issue 5 (9th May 2022) - Solanki, Ravisinh; Patel, Chhaganbhai; Patel, Ravi; Maradiya, Anujkumar; Parikh, Shalin; Gayakvad, Bhavinkumar
Abstract: As per the ICH M7 guideline nitrosamine impurities are referred to as cohort of concern which are having a potential significant carcinogenic risk and for the safe human consumption of drug products, the levels of nitrosamine impurities need to be controlled as per respective permissible daily exposures (PDE). An accurate, precise, sensitive, and robust UPLC-APCI-TQ-MS/MS method has been developed for the quantification of eight nitrosamine impurities in the marketed formulation of metformin and glipizide Tablets. Chromatographic separation was achieved using Kinetex ® 150 × 3.0 mm Biphenyl 100 Å, 2.6 µm column with mobile phase A (0.1% w/v formic acid dissolved in water) and mobile phase B (0.1% w/v formic acid dissolved in methanol) with a flow rate of 0.4 mL per minute having run time of 20 min with gradient mode of elution. As per ICH Q2(R1) guideline the method had been validated which demonstrates the sensitivity of the developed method with a good linearity range of 1–5 ng/mL for all eight nitrosamine impurities. The validation parameters suggest that the developed method for the simultaneous quantification of eight nitrosamine impurities in the marketed formulation of metformin hydrochloride and glipizide can be routinely applied in the quality control laboratory. Graphical Abstract: UF0001